Influência do Tratamento Crônico com L-arginina na Função Renal de Ratos Submetidos a um Modelo Experimental de Doença Renal Crônica/ Influence of Chronic Treatment with L-arginine on Renal Function in Rats Subjected to an Experimental Model of Chronic Ki - Letícia Pereira de Castro; Niara da Cunha Borges; Patrícia Benício Laira; Nilo César do Vale Baracho (Revista Ciências em Saúde, 2015)
Objective: To investigate possible improvements in renal function in rats undergoing chronic renal failure treated with L-arginine. Methods: 28 rats were divided into 4 groups: Control L1- (N=7): treatment with distilled water; L2 - Moderate Uremia (N=7): supplementation with L-arginine (100 mg/kg) with unilateral nephrectomy + nephrectomy ¾ kidney against side; L3 - Moderate Uremia (N=6): supplementation with L-arginine (200 mg/kg) with unilateral nephrectomy + nephrectomy ¾ kidney against side; L4 - Moderate Uremia (N=8): supplementation with L-arginine (500 mg/kg) with unilateral nephrectomy + nephrectomy ¾ kidney against side. Results: Continuous administration of arginine L produced no significant change in creatinine dosage, urea and total protein. In glycemia L2 and L2 albumin there were minor changes. In fluid intake there were specific changes on days 6 and 8, only between L2 and control groups. Analyzing food intake, there were only significant changes (p <0.05) spot, on 5, 7 and 9 between L2 and L1 compared with the control, respectively. Regarding the urinary debit, there were significant change (p <0.01) between L3 and control. Conclusion: It was observed that L-arginine supplementation has no effect on renal failure, does not produce improvements in urea, creatinine, total protein and urinary debit. However, it produces changes in blood glucose and albumin, finding a standard dose response in statistical analysis.